1989
DOI: 10.1111/j.1365-2621.1989.tb04685.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing Parameters of Chymosin Extraction by Ultrasound

Abstract: Control method for chymosin productionConventional chymosin (rennin) production requires a prolonged cxtraction. An ultrasound method of chymosin extraction was dcvcloped for increased efficiency. Ultrasound extraction was carried out with Tekmar sonic disruptor (TK 1000) and Lauda circulator. Control cxtraction was carried out by shaking. The USC of ultrasound rcsultcd in a significant reduction of extraction time with increases in activity and yield of chymosin. The optimal parameters for ultrasound extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Chymosin extractions by ultrasound were carried out with a Tekmar TK 1000 sonic disrupter (Tekmar, Cincinnati, OH) and Lauda circulator, model K-2/R (Brinkmann, Westbury, NY), which was used for cooling and maintaining temperature of the extraction mixture. The optimal parameters of ultrasound extraction established in a previous study (Kim and Zayas, 1989) were used for these experiments: specific intensity, 36 W/cm* at 20 kHz frequency; extraction time, 80 min; extraction temperature, 25°C; ratio of abomasa to NaCl solution, Frozen abomasr stored at -25OC 1:25; and activation time of prochymosin, 13.0-13.5 hr. Other parameters of ultrasound extraction were the same as those of the control method.…”
Section: Ultrasound Methods For Chymosin Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chymosin extractions by ultrasound were carried out with a Tekmar TK 1000 sonic disrupter (Tekmar, Cincinnati, OH) and Lauda circulator, model K-2/R (Brinkmann, Westbury, NY), which was used for cooling and maintaining temperature of the extraction mixture. The optimal parameters of ultrasound extraction established in a previous study (Kim and Zayas, 1989) were used for these experiments: specific intensity, 36 W/cm* at 20 kHz frequency; extraction time, 80 min; extraction temperature, 25°C; ratio of abomasa to NaCl solution, Frozen abomasr stored at -25OC 1:25; and activation time of prochymosin, 13.0-13.5 hr. Other parameters of ultrasound extraction were the same as those of the control method.…”
Section: Ultrasound Methods For Chymosin Extractionmentioning
confidence: 99%
“…Ultrasound causes destruction of cellular structure by a cavitation effect (Hughes and Nyborg, 1962) and increases the activity of substances that are bound in cell structures (Fry, 1978). In our previous study (Kim and Zayas, 1989), the optimal parameters of ultrasound for chymosin extraction were established and greater yield of chymosin was reported with increased activity from the ultrasound treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experimental data, the maximum predictable extraction yield for the ultrasonic extraction of goat kid rennet was obtained under the following conditions: ultrasound intensity of 44 W/cm 2 , extraction time of 25 min, NaCl concentration of 16% and the ratio of abomasumal mucosa to extraction solution of 1 : 30. These optimal parameters were different from those recommended by Kim and Zayas (1989), possibly due to the differences of tissue structure between calf and goat kid abomasums.…”
Section: Resultsmentioning
confidence: 62%
“…However, in conventional extraction methods, the extraction process involved a long time (about 72 h), which has a detrimental effect on the quality of rennet, particularly on its activities and microbial contamination (Zayas 1986, 1987). The application of ultrasound for the extraction of calf rennet has been studied and it was found that ultrasonic extraction not only greatly shortened the extraction time, but also increased the activity and yield of calf rennet (Zayas 1986; 1987; Kim and Zayas 1989). However, there have been few reports on the application of ultrasound for the extraction of goat kid rennet.…”
Section: Introductionmentioning
confidence: 99%
“…An ultrasound method of chymosin extraction was developed for increased efficiency (Kim and Zayas 1989). The use of ultrasound resulted in a significant reduction of extraction time with increases in activity and yield of chymosin.…”
Section: Introductionmentioning
confidence: 99%